Importância das aulas experimentais e lúdico para ensino de ciências - SOUSA, Maria dos Reis Araujo de (Universidade Federal do Tocantins, 2023)
This work aims to present the importance of experimental and playful classes that help in the learning process in Science teaching. The methodology used to carry out this study was through descriptive research with a qualitative approach. In order to carry out this work, a questionnaire was applied to ten elementary school teachers to find out what their conception regarding the application of playful and experimentais classes. The results found show that experimentation and play are not always achieved the expected goals, due to the lack of laboratory and even adequate spaces to carry them out. Although some schools do not have or do not provide laboratories, it is possible to carry out the activities even inside the classroom